Comparison of Der p1-specific antibody levels in children with allergic airway disease and healthy controls - (:unkn) unknown (WILEY, 2007)
Although children, with allergic airway disease, who are sensitized to house-dust mite (HDM) are known to have increased levels of allergen-specific IgE and IgG, the association between the quantity of those immunoglobulins and the clinical features of disease is not yet well established. The purpose of this study was (i) to evaluate Der p1-specific IgA, IgG1, IgG4, and IgE levels of children with HDM-allergic asthma and allergic rhinitis and to compare it with that of healthy controls (ii) to assess the association with disease duration. A total of 73 patients were included. Of those, 58 had asthma (M/F: 27/31, mean age 7.9 +/- 2.7 yr) and 15 were diagnosed as allergic rhinitis (M/F: 8/7, mean age 10.1 +/- 4.0 yr) without asthma. Twenty-five (M/F: 13/12, mean age 9.5 +/- 4.2 yr) non-allergic children were included as healthy controls. Data on age at onset and duration of disease were recorded. Then, Der p1-specific IgA, IgG1, IgG4, IgE levels were measured in all of the 98 subjects by ELISA. Comparison of Der p1-specific antibody levels of patients and controls revealed that Der p1-specific IgG1, IgG4 and IgE levels of patients with asthma (p = 0.012, p = 0.021, p = 0.004, respectively) were significantly higher than healthy controls. Also, the ratio of Der p1-specific IgA/IgE was significantly lower in asthmatic children when compared with children with allergic rhinitis and controls (p = 0.029, p < 0.001, respectively). Der p1-specific IgG1, IgG4, IgE and IgA levels of asthmatic children with duration of disease of >= 4 yr were significantly higher than those with disease duration of < 4 yr. IgA/IgE ratio was not significantly different in those two groups of asthmatics. We concluded that although all of the specific antibody levels increased with longer duration of asthma, IgA/IgE ratio remains to be low in asthmatic children allergic to HDM.
Keywords: asthma; children; Der p1-specific-antibody; house-dust-mite; BRONCHIAL-ASTHMA; IGE ANTIBODIES; IGG4; MITE